Engineering properties and microstructure of brickwork under aggressive environment - Wan Ibrahim, Mohd Haziman (2011)
The influence of aggressive environmental exposures on the mechanical properties and performance of masonry systems has been investigated. The investigation involved the measurement of moisture movement, strength and modulus of elasticity of single leaf masonry walls which were built from fired-clay and calcium silicate bricks in conjunction with designation (iii) mortar with proportions of 1: 1: 6 (OPC: lime: sand). After being constructed, the masonry walls were cured under polythene sheet for 14 days in a controlled environment room with temperature of 20±5ºC and 80±5% relative humidity. They were then exposed to sodium sulphate, sodium chloride and sodium sulphate-sodium chloride solutions at different concentrations of 5, 10 and 15%. The strength and elastic modulus of the brick walls were determined at the ages of 28, 56, and 180 days. At the same time, the moisture movement of the brick walls was monitored up to 210 days. The moisture movement, strength and modulus of elasticity were also measured on the unbonded bricks and mortar prism so that the contribution of brick types and mortar on the deformation of the masonry walls could be quantified. In addition, the properties of companion control walls, brick units and mortar were also assessed so that the effects of the aggressive exposure conditions could be quantified. XRF analysis was also carried out to determine the actual elements in the masonry materials before being exposed to soluble salts. XRD, SEM and EDX analysis were conducted after 180 days to observe the compounds developed after the exposure the soluble salts. As a result, after the period of exposure to the soluble salt conditions, large expansion and reduction in strength as well as elasticity of masonry wall were observed in particular for the case of sulphate exposures. These are mainly associated with the formation of ettringite crystals in the mortar, inducing expansion, cracking and disintegration of the mortar which led to the disintegration of the masonry walls. The formation of thenardite was observed in the fired-clay and calcium silicate brick due the exposure to sulphate, whereas halite formation was observed for the case of calcium silicate brick and mortar, due the exposure to chloride, but they did not cause any significant effect on the masonry walls. The composite model underestimated the modulus of elasticity and moisture movement of masonry wall which were exposed to the aggressive environments. Both the fired-clay and calcium silicate masonry walls exhibited better performance in chloride environment than in sulphate exposure and sulphate – chloride exposure due to the formation of expansive ettringite crystals.